Design Optimization on Seawater Distillation System That Utilizes Exhaust Gas On 300 Gt Fishing Vessel - S A A Sunya; A Santoso; M B Zaman (Department of Ocean Engineering, 2023)
In the shipbuilding process, planning and calculations are needed, including the planning of the existing systems on the ship, one of which is the freshwater supply system. In planning the freshwater supply system, it is necessary to calculate the fresh water tank, which depends on several parameters such as; length of sailing time, number of ship passengers, and others. There are two options to supply the large freshwater needs, either providing a large tank capacity or a freshwater production system (seawater treatment). However, providing a large space for freshwater tanks will reduce the payload of the ship. Most of the generators' diesel engine combustion can be used to maximize the heat energy wasted through the generators’ diesel engine exhaust gases. The solution that will be pursued is the distillation of seawater into freshwater by utilizing the heat energy of engine exhaust gases, which so far have not been optimally utilized on fishing vessels. In this project, we will discuss the use of exhaust gas for the design optimization of a seawater distillation system that utilizes exhaust gas on a 300 GT fishing vessel.